Fibroblasts as key effectors of acupuncture in treatment of rheumatoid arthritis - Tu, Shi-Wei; Kawanokuchi, Jun; Takagi, Ken; Liu, Yang-Yang; Li, Jun-Yi; Deng, Kai-Yuan; Li, Yan-Wei; Yao, Kai-Fang; Chen, Zhi-Han; Fan, Ze-Zhi; Xu, Zhi-Fang; Sa, Yu-Ping; et al. (Frontiers in Immunology, 2026)
Rheumatoid arthritis (RA) is a chronic autoimmune disease characterized by synovial inflammation, cartilage degradation, and bone erosion. The diseases also involves pathological changes in the surrounding fascial tissues that lead to persistent pain. Current clinical treatments rely primarily on non-steroidal anti-inflammatory drugs and analgesics, which often have limited efficacy and potential side effects. Manual acupuncture (MA), a traditional therapeutic modality, has shown promising effects in alleviating RA-related symptoms. However, the underlying mechanisms remain largely unclear. Fibroblasts, which are known for their mechanosensitivity and immunomodulatory functions, may play a crucial role in mediating the therapeutic effects of acupuncture. In this study, we demonstrated that MA significantly ameliorated pathological changes in joint-associated fascia in a murine model of adjuvant-induced arthritis with minimal impact on bone and cartilage morphology. Post-acupuncture analysis revealed the upregulation of extracellular matrix (ECM)-related genes and proteins, such as fibromodulin, collagen I, and hyaluronan synthase 2, along with increased expression of mechanosensitive molecules, including Piezo1, Ras homolog family member A (RhoA), and Yes-associated protein 1 (YAP1). Moreover, local changes were observed in the expression of fibroblast-associated markers including Fibroblast Growth Factor 2 (FGF-2), Fibroblast Growth Factor 7 (FGF-7), Fibroblast-Specific Protein 1 (FSP-1), Cannabinoid Receptor 2 (CB2), and Proliferating Cell Nuclear Antigen (PCNA). Notably, selective ablation of fibroblasts in the acupoint area via recombinant adeno-associated virus -mediated apoptosis significantly attenuated the analgesic effect of acupuncture, accompanied by reduced collagen fiber deposition, decreased mast cell degranulation, and downregulation of ECM components and regulatory molecules, such as Hyaluronan Binding Protein 2 (HABP2) and CB2. In conclusion, the study findings suggest that acupuncture alleviates RA-induced pathological and pain responses by activating fibroblasts in the fascial tissue. This mechanotransduction process likely involves the downstream modulation of cannabinoid receptors and ECM-related proteins, including hyaluronic acid and collagen.